St. Lucia : Staff Report for the 2000 Article TV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2000 Article IV Consultation highlights that after a period of slow growth in the mid-1990s, mainly owing to a decline in banana output, economic growth of St. Lucia has improved since 1998. In 1998-99, real GDP rose by an average of 3 percent a year. Executive Directors have stressed that further diversification and enhancements to international competitiveness are needed to permanently raise long-term growth and to reduce the external vulnerability of the economy, particularly in light of the market uncertainties facing the crucial banana industry.